Glycosylated hemoglobin level and number of oral antidiabetic drugs predict whether or not glycemic target is achieved in insulin-requiring type 2 diabetes. Issue 2 (April 2015) - Lin, Shi-Dou; Tsai, Shih-Tzer; Tu, Shih-Te; Su, Ching-Chieh; Chen, Jung-Fu; Lu, Chieh-Hsiang; Wang, Chao-Hung; Yu, Neng-Chun; Hsu, Shang-Ren; Hsieh, Ming-Chia
Abstract Aims Factors predicting success (glycosylated hemoglobin (A1C) < 7%) with insulin therapy in patients with insulin-requiring type 2 diabetes need to be identified. Methods A retrospective, multi-center, observational study was conducted for outpatients with oral antidiabetic drug (OAD)-treated type 2 diabetes whose A1C levels remained above 7%. Patients were begun on basal insulin between January 2005 and December 2006. Biochemical variables and demographic data were collected before and after 52 weeks of insulin therapy. Results A total of 565 patients (age, 60.4 ± 11.9 years; A1C levels, 10.11 ±1.81%; duration of diabetes, 11.5 ± 6.8 years) were studied. By study end, 63 patients (11.2%) had achieved the glycemic goal (A1C < 7%). The glycemic goal attainment rate was only 9.1% in patients with A1C > 8.8% and who were taking >2 OADs at baseline. The highest rate (32.7%) of successful glycemic control was observed in the group of patients with A1C ≤ 8.8% and who used ≤ 2 OADs at baseline. Conclusions Insulin-naïve diabetic patients with A1C > 8.8%, especially those who are taking >2 OADs, have small chance to achieve good glycemic control with adding only basal insulin therapy.